KOMUNIKASI PUBLIK DINAS KOMUNIKASI DAN INFORMATIKA DALAM MENGINFORMASIKAN KEBIJAKAN PEMERINTAH (Universitas Negeri Surabaya, 2023)
Public communication is an important part of informing government policy. It has become the main task and function of the Office of Communication and Informatics to inform government policies. This study aims to find out how the implementation of public communication in the Office of Communication and Informatics informs government policy. This research is a qualitative research using descriptive analysis research method. Data collection was obtained through in-depth interviews with eight informants, four of whom were from the Office of Communication and Informatics and four members of the Sidoarjo youth organization. Data from the interviews were validated using documentation. The results of this study indicate that the Office of Communication and Informatics as the sender has not been maximal in implementing government policy information and the youth members of Sidoarjo have not received information on government policies as message recipients.